Historical benchmarks for medical therapy trials in surgery- and radiation-refractory meningioma: a RANO review. (4th February 2014) - Kaley, Thomas; Barani, Igor; Chamberlain, Marc; McDermott, Michael; Panageas, Katherine; Raizer, Jeffrey; Rogers, Leland; Schiff, David; Vogelbaum, Michael; Weber, Damien; Wen, Patrick
Abstract: Background: The outcomes of patients with surgery- and radiation-refractory meningiomas treated with medical therapies are poorly defined. Published reports are limited by small patient numbers, selection bias, inclusion of mixed histologic grades and stages of illness, and World Health Organization (WHO) criteria changes. This analysis seeks to define outcome benchmarks for future clinical trial design. Methods: A PubMed literature search was performed for all English language publications on medical therapy for meningioma. Reports were tabulated and analyzed for number of patients, histologic grade, prior therapy, overall survival, progression-free survival (PFS), and radiographic response. Results: Forty-seven publications were identified and divided by histology and prior therapies, including only those that treated patients who were surgery and radiation refractory for further analysis. This included a variety of agents (hydroxyurea, temozolomide, irinotecan, interferon-α, mifepristone, octreotide analogues, megestrol acetate, bevacizumab, imatinib, erlotinib, and gefitinib) from retrospective, pilot, and phase II studies, exploratory arms of other studies, and a single phase III study. The only outcome extractable from all studies was the PFS 6-month rate, and a weighted average was calculated separately for WHO grade I meningioma and combined WHO grade II/III meningioma. For WHO I meningioma, the weighted average PFS-6 was 29% (95% confidence interval [CI]: 20.3%–37.7%). For WHO II/III meningioma, the weighted average PFS-6 was 26% (95% CI: 19.3%–32.7%). Conclusions: This comprehensive review confirms the poor outcomes of medical therapy for surgery- and radiation-refractory meningioma. We recommend the above PFS-6 benchmarks for future trial design.